The Child Archetype in A. Platonov’s Short Novel “The Foundation Pit" - Мкртчян, Марианна (Bulletin of Yerevan University H: Russian Philology, 2021)
The article examines the connection between fiction and myth using A. Platonov’s short novel "The Foundation Pit". The analysis is based on the provisions of Jung’s analytical psychology, in particular, on his theory of archetypes. The article shows how the dream of building the future is accompanied by a deep search for the truth and is closely connected with a theme of childhood. Comparative analysis of the image of Nastya in "The Foundation Pit" with a child archetype described by Jung in his work "The